STEM‐CL investigations on the influence of stacking faults on the optical emission of cubic GaN epilayers and cubic GaN/AlN multi‐quantum wells. Issue 4 (27th February 2015) - Kemper, R. M.; Veit, P.; Mietze, C.; Dempewolf, A.; Wecker, T.; Bertram, F.; Christen, J.; Lindner, J. K. N.; As, D. J.
Abstract: We report the influence of {111} stacking faults on the cathodoluminescence (CL) emission characteristics of cubic GaN (c‐GaN) films and cubic GaN/AlN multi‐quantum wells. Transmission electron microscopy (TEM) measurements indicate that stacking faults (SFs) on the {111} planes are the predominant crystallographic defects in epitaxial films, which were grown on 3C‐SiC/Si (001) substrates by plasma‐assisted molecular beam epitaxy. The correlation of the SFs and the luminescence output is evidenced with a CL setup integrated in a scanning TEM (STEM). By comparing the STEM images and the simultaneously measured CL signals it is demonstrated that SFs in these films lead to a reduced CL emission intensity. Furthermore, the CL emission intensity is shown to increase with increasing film thickness and decreasing SF density. This correlation can be connected to the reduction of the full width at half maximum of X‐ray diffraction rocking curves with increasing film thickness of c‐GaN films. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)